The Impact of Technoference on Parenting Styles towards Children - Tarigan, Ribkha Esterlina; Setiasih , Setiasih (Journal La Edusci, 2025)
The This study examines the impact of technoference on parenting styles and its implications for children’s development. Technoference, defined as interruptions in family interactions caused by technology use, poses significant challenges to effective parenting. This quantitative study employs a cross-sectional survey method, involving 60 parents with children aged 7-10 years. Data were collected using standardized instruments, including the Technoference Scale, Parenting Style Questionnaire, and Child Social-Emotional Development Scale. Descriptive statistics, correlation, regression, and moderation analyses were conducted to analyze the data. Results reveal a moderate level of technoference among parents, which correlates significantly with children’s cognitive and behavioral challenges. Initial abilities (????=0.850, ????<0.001) and socioeconomic status (????=0.102, ????=0.001) were strong predictors of parenting style outcomes. The interaction effect (????=0.045, ????=0.003) suggests that higher SES amplifies the positive impact of initial abilities on parenting effectiveness. The findings underscore the importance of addressing technoference and tailoring interventions to enhance both children’s abilities and parental resources. This study contributes to understanding the complexities of parenting in the digital age.